Species Distribution Model and Conservation of Mentaok (Wrightia javanica) in Indonesia - Sutomo; Humaida, Nida; Wahab, Luthfi; Saputra, Muhammad Hadi; Kurniawati, Fitri; Atmaja, Muhammad Bima; Pujiono, Eko; Sukmawati, Jalma Giring; Hani, Aditya; Iryadi, Rajif; Herningtyas, Wieke; Wahyuningtyas, Reni Setyo (Jurnal Manajemen Hutan Tropika, 2025)
The Alas Mentaok was a forest dominated by the mentaok tree (Wrightia javanica) that once existed in Yogyakarta, Java Island, Indonesia. This forest has cultural and historical value, as it is believed to be the first location to establish the Mataram Islam Kingdom in Java in 1582 AD. This study utilized species distribution models (SDMs) to investigate the species distribution pattern and assess its latest conservation status in Java and the Lesser Sunda Islands, Indonesia. The methodology used involved collecting occurrence and environmental data of W. javanica, conducting species distribution modeling using the maximum entropy algorithm, evaluating the model's accuracy, and performing an independent assessment of the area of occupancy (AOO) and extensive occurrence (EOO) using the geospatial conservation assessment tool (GeoCAT). While the number of suitable habitat areas for W. javanica in Yogyakarta is projected to decrease by 2100, the islands of Sumba and Timor are anticipated to experience an increase in the suitable habitat areas for the species during the same year. The analysis of BIOCLIM 34 indicates the mean moisture index of the warmest quarter plays a vital role in the current and future projections. AOO calculation in GeoCAT places this species in the endangered (EN) category, particularly within our regions of interest in Java and the Lesser Sunda Islands. Overall, a full assessment combining a habitat suitability model with current conservation status information would provide a more comprehensive understanding of mentaok's habitat preferences and current conservation status in Indonesia.